Ethnic variations in compulsory detention under the Mental Health Act: a systematic review and meta-analysis of international data - Barnett, P; Mackay, E; Matthews, H; Gate, R; Greenwood, H; Ariyo, K; Bhui, K; Halvorsrud, K; Pilling, S; Smith, S (Elsevier, 2019)
Background Evidence suggests that black, Asian and minority ethnic (BAME) groups have an increased risk of involuntary psychiatric care. However, to our knowledge, there is no published meta-analysis that brings together both international and UK literature and allows for comparison of the two. This study examined compulsory detention in BAME and migrant groups in the UK and internationally, and aimed to expand upon existing systematic reviews and meta-analyses of the rates of detention for BAME populations. Methods For this systematic review and meta-analysis, we searched five databases (PsychINFO, MEDLINE, Cochrane Controlled Register of Trials, Embase, and CINAHL) for quantitative studies comparing involuntary admission, readmission, and inpatient bed days between BAME or migrant groups and majority or native groups, published between inception and Dec 3, 2018. We extracted data on study characteristics, patient-level data on diagnosis, age, sex, ethnicity, marital status, and occupational status, and our outcomes of interest (involuntary admission to hospital, readmission to hospital, and inpatient bed days) for meta-analysis. We used a random-effects model to compare disparate outcome measures. We assessed explanations offered for the differences between minority and majority groups for the strength of the evidence supporting them. This study is prospectively registered with PROSPERO, number CRD42017078137. Findings Our search identified 9511 studies for title and abstract screening, from which we identified 296 potentially relevant full-text articles. Of these, 67 met the inclusion criteria and were reviewed in depth. We added four studies after reference and citation searches, meaning 71 studies in total were included. 1 953 135 participants were included in the studies. Black Caribbean patients were significantly more likely to be compulsorily admitted to hospital compared with those in white ethnic groups (odds ratio 2·53, 95% CI 2·03–3·16, p<0·0001). Black African patients also had significantly increased odds of being compulsorily admitted to hospital compared with white ethnic groups (2·27, 1·62–3·19, p<0·0001), as did, to a lesser extent, south Asian patients (1·33, 1·07–1·65, p=0·0091). Black Caribbean patients were also significantly more likely to be readmitted to hospital compared with white ethnic groups (2·30, 1·22–4·34, p=0·0102). Migrant groups were significantly more likely to be compulsorily admitted to hospital compared with native groups (1·50, 1·21–1·87, p=0·0003). The most common explanations for the increased risk of detainment in BAME populations included increased prevalence of psychosis, increased perceived risk of violence, increased police contact, absence of or mistrust of general practitioners, and ethnic disadvantages. Interpretation BAME and migrant groups are at a greater risk of psychiatric detention than are majority groups, although there is variation across ethnic groups. Attempts to explain increased detention in ethnic groups should avoid amalgamation and instead carry out culturally-specific, hypothesis-driven studies to examine the numerous contributors to varying rates of detention. Funding University College London Hospitals National Institute for Health Research (NIHR) Biomedical Research Centre, NIHR Biomedical Research Centre at South London and Maudsley NHS Foundation Trust, King's College London, and NIHR Collaboration for Leadership in Applied Health Research and Care North Thames at Bart's Health NHS Trust.